Reservoir sedimentation handbook : design and management of dams, reservoirs, and watersheds for sustainable use - Morris, Gregory L. (McGraw-Hill, 1998)
This book contains: Reservoirs and Sustainable Development; Engineering Features of Dams and Reservoirs...